1961
DOI: 10.1111/j.2042-7158.1961.tb11898.x
|View full text |Cite
|
Sign up to set email alerts
|

The Mode of Action of Penicillin

Abstract: ALTHOUGH penicillin has been used successfully in clinical medicine for some 20 years its precise mode of action has until recently been ill understood. Now, progress can be reported.Previous reviews on its mode of action have been published by Rinderknecht (1 946), Pratt and Dufrenoy (1 947) and Eagle and Saz (1 955), and Stenlake (1959) has recently summarised the actions of various antibiotics. Because one of the main effects of penicillin appears to be concerned with an inhibition of bacterial cell wall sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1963
1963
1976
1976

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…However, we have found that the activity of soluble RNA seems to be affected (to be published) and this is reasonable, since uridylic and cytidylic compounds accumulate during penicillin action (Strominger, 1960;Saukkonen, 1961) and the re-utilization of these mucleotides may thus be blocked. Several investigators (Prestidge & Pardee, 1957; Hugo & Russell, 1961) have suggested that penicillin may have an additional action beside that of the inhibition of cell-wall synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we have found that the activity of soluble RNA seems to be affected (to be published) and this is reasonable, since uridylic and cytidylic compounds accumulate during penicillin action (Strominger, 1960;Saukkonen, 1961) and the re-utilization of these mucleotides may thus be blocked. Several investigators (Prestidge & Pardee, 1957; Hugo & Russell, 1961) have suggested that penicillin may have an additional action beside that of the inhibition of cell-wall synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the extensive literature on penicillin action (see review by Hugo & Russell, 1961) the methods of observation normally used are measurements of viable count, which takes 48 hr., and minimal inhibitory concentration (MIC), which takes 241 hr.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation